Protagonistas no palco do cotidiano: mulheres da comunidade Quilombola do Morro do Boi, Balneário Camboriú, Santa Catarina - Silva, Camila Evaristo da (2016)
This paper presents considerations about women experiences in the Quilombola Community of Morro do Boi, in Balneário Camboriú/SC, focusing on scenes of three women trajectories: Sueli Marlete Leodoro, the daughter; Margarida Jorge Leodoro, the mom; and Sayonara Nancy Leodoro Siqueira, the granddaughter. It happens in a period not counted in western epistemologies: the period of matriarch. Through their trajectories, issues that transcend their experiences are analyzed, common to other actors/actresses of that community, particular of each generation. We propose to use as sources, oral testimony, aided by field research, the black movement productions exhibited virtually, laws, audiovisual productions, pictures and he Anthropological Report of Morro do Boi Community. We aim to understand how political deals about better life conditions are configured and experienced and how the micro-Africas in the Quilombola Community of Morro do Boi are preserved from a gender perspective